A new perspective on hydrogen diffusion and hydrogen embrittlement in low-alloy high strength steel. (September 2020) - Cheng, X.Y.; Zhang, H.X.
Highlights: First propose multiple hydrogen trap sites around dislocation core and simply obtained trap sites density. First present the activation energy for hydrogen diffusion a clear physical interpretation. Fractions of hydrogen occupied in normal lattice and traps depend on charging condition, not vary with trap sites density. HIE was resulted from higher trap sites density and higher hydrogen concentration. The sensitivity of internal hydrogen embrittlement can be well evaluated. Abstract: Hydrogen diffusion and hydrogen induced embrittlement have been studied in low-alloyhigh strength steel tempered at three different temperature using electrochemical permeation and mechanical tensile tests, respectively. After multiple hydrogen trap sites around dislocation core was first proposed, the quantitative relations between hydrogen diffusivity, hydrogen concentration, as well as activation energy for hydrogen diffusion and hydrogen trap sites density were developed. In addition, the hydrogen-induced embrittlement would result from higher trap density and higher hydrogen concentration. Hence the connection among hydrogen diffusion, microstructure and hydrogen induced embrittlement were established where the hydrogen trap sites density served as a bridge.